Portrait of Datu Kalampayan Religious Tourism Area, Astambul District, Banjar Regency - Hapipah, Raina; Abbas, Ersis Warmansyah; Jumriani, Jumriani; Handy, Muhammad Rezky Noor; Nur'aini, Fatwa (Program Studi Pendidikan IPS, 2024)
The purpose of this study was to describe the portrait of traders as a visitor attraction in the religious tourism area of Datu Kelampayan Astambul Sub-district, Banjar Regency. Qualitative research method was used in this study to describe the general description of the location and to describe the portrait of traders as a visitor attraction in the religious tourism area of Datu Kelampayan, Astambul Sub-district, Banjar Regency. The subjects in this research are the manager of the religious tourism area, tourists who come to visit the religious tourism area, and local people who carry out trading activities in the Datu Kalampayan religious tourism area. Data collection techniques were carried out using observation, interviews and documentation. Data analysis uses data reduction based on research objectives, data presentation based on description, and data withdrawal based on conclusion drawing. Test data validity with triangulation. The results showed an overview of the Datu Kalampayan religious tourism area, which has a well-organised area and has various adequate facilities for visitors to use. The portrait of traders as a visitor attraction in the Datu Kalampayan religious tourism area is carried out every day and is related to economic activities. Economic activities carried out by traders consist of production, distribution and consumption activities. The conclusion of this research is that the tourist area has various facilities that can be utilised by visitors, one of the facilities that visitors often visit is a trader's place. The existence of trading activities in the Datu Kalampayan religious tourism area is used to meet the needs of local people in their daily lives.